Pelvic-Floor Muscle Rehabilitation in Erectile Dysfunction and Premature Ejaculation. Issue 12 (1st December 2014) - Lavoisier, Pierre; Roy, Pascal; Dantony, Emmanuelle; Watrelot, Antoine; Ruggeri, Jean; Dumoulin, Sébastien
Abstract : Background: In men, involuntary or voluntary ischiocavernosus muscle contractions after erection lead to intracavernous blood pressures far higher than the systolic pressure, which builds and maintains penile rigidity. Thus, erectile dysfunction may be partly due to ischiocavernosus muscle atrophy and may be treated by rehabilitation interventions. Objective: The purpose of this study was to determine whether pelvic-floor muscle strengthening interventions could be associated with increases in intracavernous pressure that would increase penile rigidity. Design: An observational study was conducted. Methods: One hundred twenty-two men with isolated erectile dysfunction and 108 men with isolated premature ejaculation participated (no neuromuscular diseases or previous perineal rehabilitation). Thirty-minute sessions of voluntary contractions coupled with electrical stimulation were designed to increase ischiocavernosus muscle strength (monitored through intracavernous pressure increase). A linear mixed-effects model per group analyzed separately, then jointly, the maximum change in pressure (ΔP) and the maximum baseline (ie, respectively, the average contraction-generated difference in intracavernous pressure and the intracavernous pressure plateau at full erection, both measured during the highest moving average of the best 2 minutes of each session). Results: Over 20 sessions, the maximum ΔP increased in erectile dysfunction as well as in premature ejaculation (87% and 88%, respectively, in men with positive trends). The maximum baseline also increased (99% and 72%, respectively, in men with positive trends). The joint modeling indicated that the mean expected progressions of the intracavernous pressure after 5 sessions in erectile dysfunction and premature ejaculation were 62.85 and 64.15 cm H2 O, respectively. Limitations: Indirect measurements were obtained of intracavernous pressure and ischiocavernosus muscle force. Conclusions: Pelvic-floor muscle rehabilitation was found to be beneficial in erectile dysfunction. However, its effects on symptoms of premature ejaculation, despite intracavernous pressure gains, were much more difficult to assess. The definitive proof of its benefits requires rather difficult-to-design clinical trials.